Controversies around educational projects for gender equality in Italy - Anedda, Ludovica (Cahiers de la Section des sciences de l'éducation, 2019)
This study explores the controversial arguments that took place around the "teoria del gender" and its perceived impact on education in Italy, particularly between 2013 and 2016. An investigation of newspaper articles, media campaigns and declarations of Catholic Church representatives shows how the "anti-gender" movements have influenced public opinion to oppose gender equality and sexuality education in schools. Through an analysis of educational projects in the municipality of Cagliari, the author highlights the main obstacles the actors of these projects had to face: a widespread lack of awareness on gender equality issues; contrasting political dynamics and interests; strong misinformation campaigns led by a mostly Catholic opposition. This study intends to provide a foundation for further research and for the development of new strategies to respond to these challenges. Education is here understood as a fundamental means to achieve gender equality, because of its potential for the deconstruction of traditional gender norms and for the development of critical thinking.